Long-Day Photoperiod Enhances Jasmonic Acid-Related Plant Defense. Issue 1 (1st August 2018) - Cagnola, Juan I.; Cerdán, Pablo D.; Pacín, Manuel; Andrade, Andrea; Rodriguez, Verónica; Zurbriggen, Matias D.; Legris, Martina; Buchovsky, Sabrina; Carrillo, Néstor; Chory, Joanne; Blázquez, Miguel A.; Alabadi, David; et al.
Abstract : Long days perceived by photosensory receptors enhance jasmonic acid-dependent resistance in Arabidopsis. Abstract: Agricultural crops are exposed to a range of daylengths, which act as important environmental cues for the control of developmental processes such as flowering. To explore the additional effects of daylength on plant function, we investigated the transcriptome of Arabidopsis ( Arabidopsis thaliana ) plants grown under short days (SD) and transferred to long days (LD). Compared with that under SD, the LD transcriptome was enriched in genes involved in jasmonic acid-dependent systemic resistance. Many of these genes exhibited impaired expression induction under LD in the phytochrome A ( phyA ), cryptochrome 1 ( cry1 ), and cry2 triple photoreceptor mutant. Compared with that under SD, LD enhanced plant resistance to the necrotrophic fungus Botrytis cinerea . This response was reduced in the phyA cry1 cry2 triple mutant, in the constitutive photomorphogenic1 ( cop1 ) mutant, in the myc2 mutant, and in mutants impaired in DELLA function. Plants grown under SD had an increased nuclear abundance of COP1 and decreased DELLA abundance, the latter of which was dependent on COP1. We conclude that growth under LD enhances plant defense by reducing COP1 activity and enhancing DELLA abundance and MYC2 expression.